Acute Issues of Strateging and Functioning of Information Space on Territory in Conditions of Restrictive Measures - T. M. Odintsova; E. A. Matushevskaya; N. Yu. Shipilov; M. G. Rozhkova (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The article studies such issues as strateging of sustainable development of regions, developing the system of information support of strategic development of the region, risks connected with sanctions imposed by Western countries. These subjects were analyzed with the help of literature sources and further lines of research were proposed. The system of information support of strategic development of regions includes strategic goals and figures of development, which require correction in conditions of growing pressure on behalf of Western countries, as well as political and economic restriction of external environment. The authors came to the conclusion about the necessity to correct the system of indicators of the region strategic development by social and economic expediency, managerial supervision and possibility of monitoring. During designing, realizing and monitoring of strategy of region development it is necessary to take into account the impact not only of conventional restrictions coming from the external environment but also specific restrictions in conditions of sanctions imposed by Western countries. Such restrictions during the last decade turned into a trend, which affects life of territories with uncertain status, unrecognized and questionable territories and tend to be used as tools of political pressure or economic wars.